Dose-response relationship of resistance training for muscle morphology and strength in elderly cancer patients: A meta-analysis - Zhai, Haiting; Wei, Hongwen; Xia, Jixiang; Wang, Wei (Frontiers in Medicine, 2023)
Objective To systematically evaluate the effects of resistance training (RT) on muscle strength and muscle hypertrophy in elderly cancer patients, and to provide dose–response relationships of RT variables that could improve muscle strength and morphology in elderly cancer patients. Method The Review Manager 5.3 was applied to analyze the 12 literatures (616 participants) through random or fixed effects model and global effect size to examine upper limb strength, lower extremity strength, and muscle hypertrophy. Sub-group analysis was made on five variables: the total number of repeated training times/week, load intensity, exercise frequency/week, exercise duration and gender. This study also examines the heterogeneity and publication bias. Results Twelve literatures (616 participants, 60–80 years) were included in meta-analysis. RT significantly increased the upper limb muscular strength (SMD = 0.51, 95% CI: 0.10–0.93; Z = 2.41; p = 0.02) and lower extremity strength (SMD = 0.48, 95% CI: 0.28–0.67; Z = 4.82; p < 0.00001), but had no significant effect on muscle morphology(SMD = 0.21, 95% CI: 0.01–0.42; Z = 1.88; p = 0.06). In subgroup analysis for lower extremity muscle strength in elderly male cancer patients, it was found that male intensity of 70–90%1RM, volume of 400–500 times per week, frequencies of 3 times per week, and session of 12–24 weeks, revealed the greatest effect. Funnel plot of the three studies shows that the results were reliable, and no publication bias was found. Conclusion RT had medium effects on improving muscle strength in elderly cancer patients, but it is not effective in improving muscle hypertrophy. In addition, when RT is performed, different training protocols can have an effect on the growth of muscle strength. Therefore, a lower extremity training protocol with a training intensity of 70–90% 1RM, a total of 400–500 repetitions per week, 3 times per week, and an exercise session of 12–24 weeks is most effective in improving lower extremity strength in elderly male cancer patients.